EFEKTIVITAS TERAPI AKUPRESUR TERHADAP PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI SEBAGAI PENERAPAN HOLISTIC CARE: A LITERATURE REVIEW (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2024)
Acupressure therapy is a type of non-pharmacological therapy that can reduce blood pressure in hypertensive patients. Apart from being easy to do, it is also cost-effective and does not cause side effects. Acupressure therapy aims to help hypertension sufferers by lowering blood pressure and reducing long-term side effects of drug therapy, such as nausea, vomiting, headaches, and dizziness. Research on acupressure not only provides therapeutic effects and provides comfort for hypertension sufferers, but also improves the patient's quality of life. Objective: This study aims to evaluate the effect of acupressure on reducing hypertension. Research Method: A literature review that focuses on acupressure therapy interventions to reduce blood pressure in hypertensive patients. The article search method used PICOTT questions in the Science Direct, EBSCO, PubMed, and Google Scholar databases by entering the keywords Hypertension, Acupressure, and Blood pressure. The search was limited to full-text articles, original research, as well as national and international journals, published in 2015-2024, of which 16 journals were found. Results: This literature review study significantly resulted in the conclusion that acupressure therapy can be used as an alternative treatment for reducing blood pressure in hypertensive patients. Conclusion: Acupressure therapy as an evidence-based practice in improving holistic patient care, provides a safe and effective non-pharmacological alternative in the management of high blood pressure.
Keywords: Hipertensi; Akupresur; Tekanan Darah